Proceedings of the 22nd ACM Conference on Virtual Reality Software and Technology 2016
DOI: 10.1145/2993369.2993410
|View full text |Cite
|
Sign up to set email alerts
|

Take-over control paradigms in collaborative virtual environments for training

Abstract: The main objective of this paper is to study and formalize the TakeOver Control in Collaborative Virtual Environments for Training (CVET). The TakeOver Control represents the transfer (the take over) of the interaction control of an object between two or more users. This paradigm is particularly useful for training scenarios, in which the interaction control could be continuously exchanged between the trainee and the trainer, e.g. the latter guiding and correcting the trainee's actions. The paper presents the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
(10 reference statements)
0
4
0
Order By: Relevance
“…The trainee had the control of the boat but the trainer could assume control at any time if the boat was about to collide with an obstacle. The study showed that the users preferred smooth transition over the sudden one by the trainer and experienced an increased level of awareness and informativeness when the visual feedback was present of the obstacles [36].…”
Section: Gestural Interactionmentioning
confidence: 95%
See 2 more Smart Citations
“…The trainee had the control of the boat but the trainer could assume control at any time if the boat was about to collide with an obstacle. The study showed that the users preferred smooth transition over the sudden one by the trainer and experienced an increased level of awareness and informativeness when the visual feedback was present of the obstacles [36].…”
Section: Gestural Interactionmentioning
confidence: 95%
“…• Collaboration/Interactivity: The complicated concept of having two or more users of the same VRE interacting with each other and with objects of the environment raising issues like co-location collision, take-over control, gestural interactions, and locomotion [35,36]. • Visual and audio fidelity: An umbrella term used to address technical issues such as synchronization of animation and sound, visual info and communication, inventory, user experience visual fidelity synchrony, and more [37].…”
Section: Vre As a Toolmentioning
confidence: 99%
See 1 more Smart Citation
“…Gaze‐based techniques and attention guiding techniques are alternatives for selecting and targeting items, or even interacting with a VR keypad . The willingness of users can be strengthened through practice in VR, such as spider phobia treatment, studying Japanese language and culture, collaborative training, and interaction with patients . Differentiated instruction provides differing teaching and learning materials .…”
Section: Related Workmentioning
confidence: 99%